Development of E-Comic-Based Learning Media Using Pixton in Theme 7 Sub-theme 2 in Class V SDN 101775 Sampali T.A 2022/2023 - Nurmayani; Yunita Sari Sinaga (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to produce a learning media in the form of E-Comic using Pixton which is feasible, effective and practical. The type of research used is research and development (R&D) which has a 4D development model developed by Thiagarajan namely Define, Design, Develop, and Disseminate. The instruments used to collect data were teacher interviews, material and media validation questionnaires, educational practitioner (teacher) questionnaires, and test questions for students. The results of this study show that the validation of media experts gets a percentage of 97.27% after revision with the